Recent Publications upon Economics (Quarterly Journal of Economics, 1905)
Journal Article Recent Publications upon Economics Get access The Quarterly Journal of Economics, Volume 20, Issue 1, November 1905, Pages 168–182, https://doi.org/10.1093/qje/20.1.168 Published: 01 November 1905